Análisis comparativo de la situacion financiera de la empresa agrorepuestos lovato s.a. en el periodo 2019 y 2020 - Varas Monserrate, Julisa Melany (2021)
This case study is based on the analysis of the economic situation as a result of COVID 19, how their accounts were affected during the confinement period and its impact on profitability, solvency and liquidity compared to 2019. This This work is called "COMPARATIVE ANALYSIS OF THE FINANCIAL SITUATION OF THE COMPANY AGROREPUESTOS LOVATO SA IN THE PERIOD 2019 AND 2020. The company Agrorepuestos Lovato S.A with Ruc 0992517026001 is a company dedicated to the commercialization of spare parts and agricultural machinery and implements located in the city of Guayaquil, it has four other branches located in the cities of; Babahoyo, Daule, Samborondón and Quito. In 2020 many companies went through the crisis that devastated COVID 19, Lovato was one of them, presenting a very significant drop in its sales of 8.87% compared to the sales of 2019, directly affected its cash equivalent, Furthermore, its accounts receivable were not allowed during the months of confinement, so it is not more than 15.06% for 2020, recovering the loan portfolio in a period of 1.71 months. Financial analyzes indicate that inventories are sold in 257 days, this being one of the main problems that affects the company's profits, that is why it is recommended that the company improve its sales strategies during this period so that it can move the inventory. both machinery and spare parts and can meet your long-term debts.